An Efficient Synthetic Protocol for Quinoxalinones, Benzoxazinones, and Benzothiazinones from 2‐Oxo‐2‐aryl‐acetyl Bromide Precursors. (27th August 2013) - Nagaraj, Muthupandi; Sathiyamoorthy, Sithuraj; Boominathan, Muthusamy; Muthusubramanian, Shanmugam; Bhuvanesh, Nattamai
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>